The genetic landscape of choroid plexus tumors in children and adults - Thomas, Christian; Soschinski, Patrick; Zwaig, Melissa; Oikonomopoulos, Spyridon; Okonechnikov, Konstantin; Pajtler, Kristian Wilfried; Sill, Martin; Schweizer, Leonille; Koch, Arend; Neumann, Julia; Schüller, Ulrich; Sahm, Felix; et al. (Neuro-Oncology, 2021)
Choroid plexus tumors (CPTs) are intraventricular brain tumors predominantly arising in children but also affecting adults. In most cases, driver mutations have not been identified, although there are reports of frequent chromosome-wide copy-number alterations and TP53 mutations, especially in choroid plexus carcinomas (CPCs).DNA methylation profiling and RNA-sequencing was performed in a series of 47 CPTs. Samples comprised 35 choroid plexus papillomas (CPPs), 6 atypical choroid plexus papillomas (aCPPs) and 6 CPCs plus three recurrences thereof. Targeted TP53 and TERT promotor sequencing was performed in all samples. Whole exome sequencing (WES) and linked-read whole genome sequencing (WGS) was performed in 25 and 4 samples, respectively.Tumors comprised the molecular subgroups “pediatric A” (N=11), “pediatric B” (N=12) and “adult” (N=27). Copy-number alterations mainly represented whole-chromosomal alterations with subgroup-specific enrichments (gains of Chr1, 2 and 21q in “pediatric B” and gains of Chr5 and 9 and loss of Chr21q in “adult”). RNA sequencing yielded a novel CCDC47-PRKCA fusion transcript in one adult choroid plexus papilloma patient with aggressive clinical course; an underlying Chr17 inversion was demonstrated by linked-read WGS. WES and targeted sequencing showed TP53 mutations in 7/47 CPTs (15%), five of which were children. On the contrary, TERT promoter mutations were encountered in 7/28 adult patients (25%) and associated with shorter progression-free survival (log-rank test, p=0.015).Pediatric CPTs lack recurrent driver alterations except for TP53, whereas CPTs in adults show TERT promoter mutations or a novel CCDC47-PRKCA gene fusion, being associated with a more unfavorable clinical course.
Advance access date 29 November 2020
Gesehen am 13.07.2021